Current state of nonengrafting donor leukocyte infusion (focus on microtransplantation for acute myeloid leukemia). Issue 6 (November 2019) - Krakow, Elizabeth F.
Abstract : Purpose of review: Microtransplantation (or micro-stem cell transplantation, MST) is one permutation of alloreactive immunotherapy increasingly studied in clinical trials. It is most commonly applied to patients with myeloid malignancies who are not suitable candidates for allogeneic hematopoietic cell transplantation. This review highlights the past 2 years of work on stem/progenitor cell products in the field of nonengrafting donor leukocyte infusion (NE-DLI), with a focus on applications of MST in acute myeloid leukemia (AML). Recent findings: Assessing the utility of MST is hampered by lack of randomized controlled trials and by variability in donor selection algorithms, treatment timing, and unknown factors. The inherent complexity of the bidirectional alloreactive reactions, implicating many cell types, makes it challenging to move beyond correlative, population-level biology toward mechanistic explanations for MST's actions in any given patient–donor pair. Yet there are indicators that by stimulating a recipient-vs.-tumor effect, MST might substantially improve complete remission rates in AML and that it might find a role in postremission therapy. Summary: The mechanistic underpinnings of MST are gradually being disentangled and its clinical development remains in early stages.